Raising students motivation for math learning using computer animation approach - Ibarra, Manuel J. (2017)
This article aims to improve the math learning process of the students in rural schools. For this purpose, a “Mathfraction” computer animation application was developed to use on the web and mobile technologies. The tool was designed using a visual approach to reinforce student’s learning process acquired in classes. The tool was tested and validated by three usability user experts, thirty four students and four teachers of two rural schools in Apurímac-Perú. Three types of tests were performed, the first one was a server’s performance test, the second one was using a user usability questionnaire and the last one was by user expert opinion questionnaire. The results of this research show that teachers and students agree that Mathfraction allows them to teach and learn math in a fun way and different from the other traditional methodologies that they knew.